The cyclic nature of innovation connecting hard sciences with soft values - Berkhout, Guus (Emerald, 2007)
This series aims to present the latest research on entrepreneurship and innovation and the impact on economic performance. Research topics covered include all aspects of entrepreneurial behavior - the determinants of research and development, intellectual property concerns, innovation within and across firms, the effect of government regulation and tax policies, patenting and other property rights issues, organizational factors, market structure effects, marketing strategies, entrepreneurship programs and other educational activities, and the relative performance of entrepreneurial firms. The disciplines covered include economics, marketing, management, finance, and history. The target audience includes both academics and practicing entrepreneurs. The overall objective is to disseminate research in a clear and effective manner to promote communication between the business and academic communities and to foster entrepreneurship within the society. A volume is published annually. It presents the latest research on entrepreneurship/innovation and the impact on economic performance. This book series is available electronically at website.
Keywords: Technological innovations -- Economic aspects.; Entrepreneurship.; elektronické knihy; electronic books